Fazenda Santa Helena : escravidão, bastardia e poder - Simonato, Juliana Sabino (2008)
This present Dissertation – Farm St. Helena: Slavery, Bastardy and Power – has the purpose to describe the mestizos 'and linings’ situation, descending of Espírito Santo black society, in the temporary cutting of the final of the century XIX and the beginning of XX. To rebuild the habitual practices of that period, it was fallen back upon the application of the method of oral history. The reports were confronted with the primary sources, what made possible a new focus and a better understanding, in relation to the practices of sociabilities that allowed, same inside the hierarchical organization of strick character, the development of favorable strategies to the ascension of some mestizos and ex-slaves. The case of Marcelino Bernardes de Souza, a great owner of lands of the area in Castello, the Baron of Guandú, with one of their slaves, it is described through the "histories" that stayed in their descendants' memory and of those who lived daily experiences in Farm St. Helena. Such situation evidences different social relationships of that established by the traditional historiography, that makes use of concepts and it creates patterns of social homogeneity, based on the defense of the existence of just gentlemen and slaves. Through the memories, kept in the memory, besides the primary sources, as inventories and books of register office, I will make a rising about the life of Marcelino, as well as I will promote the report of his/her path. I try to show some of the "spaces", found by that interbreed and lining to distance the inheritances of the captivity, due to his relationship with a member of the coffee elite of the south of Espírito Santo Province, getting to acquire, through the purchase the headquarters of the farm that belonged to his father.